The Relationship of Differential Counting with the Erythrocyte Sedimentation Rate in Patients with Typhoid Fever: Hubungan Differential Counting Dengan Laju Endap Darah Pada Penderita Demam Tifoid - Xena, Alfanny Juliannindy; Aliviameita, Andika (Indonesian Journal of Innovation Studies, 2020)
Typhoid fever is an acute systemic disease of the digestive system, and is still a global health problem faced by the international community. The incidence of typhoid fever always increases by around 500-100,000 people every year, with a mortality rate of around 0.6-5%. The purpose of this study was to determine the relationship between Differential Counting and ESR in patients with typhoid fever. The research design used is an experimental laboratory. The study sample was based on typhoid fever patients with a Widal titer 1/160 at the RSUD. R.A Basoeni Mojokerto. Differential counting examination using the automatic method with a Hematology analyzer and LED examination using the modified Westergreen method. The results showed that there was a decrease in the number of lymphocytes (60%), an increase in the number of monoit cells by 50%, and an increase in the erythrocyte sedimentation rate (53%). Based on the results of the correlation test analysis, it was found that there was no significant relationship between Differential counting and the erythrocyte sedimentation rate in patients with typhoid fever (p > 0.05).